The polytheists' statements opposing the Islamic call in light of the Holy Qur’an (Journal of the College of Basic Education, 2026)
The polytheists countered the Prophet’s (peace and blessings be upon him) call with various techniques aimed at turning people away from the path of God and distorting the truth of the Islamic religion .Among the means they resorted to were: mockery to ridicule, attacking the person of the Messenger ( peace and blessings be upon him), and attaching various accusations to him in order to turn people away from his call and weaken the resolve of the believers in him.They accused him of madness at times , and of sorcery at others , and some of them claimed that he was a poet who fabricated what he said. However, they soon found themselves impressed by the strength of his eloquence , unable to oppose him, their hearts trembling at the truth of his words even though they denied it with their tongues. At the beginning of the call, the leaders of Quraysh did not pay much attention to it, as they did not yet realize the extent of the threat it posed to their interests. But when the Quran came to expose the falsehood of their beliefs and reveal the corruption of their veneration of stones and their taking them as gods that neither benefit nor harm , the idea of​​compromise occurred to them, and their attempts began to go through several stages, which are:1- The stage of relentless efforts to extinguish the call in its infancy : From the very beginning, the Quraysh tried to extinguish the light of the call and prevent it from spreading in their society . They attempted to stop it at its root before its principles could take hold in people's hearts. They approached the Prophet (peace and blessings be upon him), offering him wealth, prestige, and power, hoping he would abandon his message and follow their desires.2- The stage of mutual appeasement and seeking coexistence without conflict : After the failure of the Quraysh's attempts to stop the call to Islam by force and enticement, they resorted to a less confrontational approach, proposing mutual appeasement. This meant that each side would refrain from criticizing the other's beliefs and allow each other to pursue their affairs and interests without interference. Their aim was to secure concessions that would preserve their interests and allow them to continue living a stable social life without direct confrontation with the call to Islam.3- The stage of negotiating conditions: After the failure of direct attempts to stop the call, the Quraysh resorted to a more cunning method, which was negotiating conditions, trying to impose restrictions that would guarantee the continuation of their influence and status amidst the spread of the call. They wanted the call to be established , but within limits that they defined, so that the wealthy and powerful would retain clear privileges that distinguished them from the general public.